Mining Criminal Administration Without Permission (PETI) Theories, Facts, And Implementation - Arif Rachman Wahyu Wicaksono; Gunarto Gunarto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aims to Obtain a new direction of PETI's criminal law enforcement that can be is implemented. Meanwhile, the research method used is a study of literature and cases around illegal and an analysis of a variety of developing thoughts and ideas. Based on the results of research and discussion, it was concluded that the implementation of the criminal administration in illegal was based on the principle of protecting common interests. The criminal application of illegal administration aspects contains three items, namely legal rules, government authority and legal relations. The legal rules are Formulated in the Mining Law and the legal relationship between the government as the mining manager and mining business stake holders through legal licensing instruments.Keywords: criminal administration; mining; licensing